2017
DOI: 10.14254/2071-8330.2017/10-4/20
|View full text |Cite
|
Sign up to set email alerts
|

Small and medium enterprises in the context of regional development and innovations

Abstract: Abstract. The current state of economic development and innovations' support often brings small and medium enterprises (SMEs) at the forefront of government fiscal policy. Various policy measures targeted at SMEs' support and development necessarily include measures on promotion of innovations within small business. However, despite substantial efforts undertaken by the authorities to increased financial injections into this area, development of innovations by small businesses faces many obstacles. Statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
2
24
0
4
Order By: Relevance
“…In Kazakhstan, the President proposed the creation of a global digital currency (cryptocurrency) as an international settlement and payment unit, as a means of preventing currency wars and speculation, distortions in trade relations, and reducing market volatility (Kulshmanov, 2017). G. F. Ruchkina notes that significant changes are coming to the banking system due to the introduction of new financial technologies, which are a serious alternative (Ruchkina et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In Kazakhstan, the President proposed the creation of a global digital currency (cryptocurrency) as an international settlement and payment unit, as a means of preventing currency wars and speculation, distortions in trade relations, and reducing market volatility (Kulshmanov, 2017). G. F. Ruchkina notes that significant changes are coming to the banking system due to the introduction of new financial technologies, which are a serious alternative (Ruchkina et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the substantial measures undertaken by authorities to increase financial support, it is found that small businesses, particularly start-ups, face some obstacles (Ruchkina, et al, 2017;Klein, et al, 2019). The most recent data show that micro-enterprises are less active in using external financial instruments than their larger peers, the reason possibly posed by difficulties in accessing them (European Central Bank, 2019).…”
Section: Microenterprises Financingtheoretical Aspectsmentioning
confidence: 99%
“…Usaha kecil dan menengah (UKM) adalah pendorong penting dari pembangunan ekonomi dan menjadi penting bagi sebagian besar ekonomi di seluruh dunia, terutama di negara berkembang dan berkembang [1], [2]. Menurut Sualang dkk [3], UMKM merupakan tulang punggung perekonomian Indonesia.…”
Section: Pendahuluanunclassified